KINETIC, THERMODYNAMIC AND MECHANISTIC FEATURES OF ESCHERICHIA COLI BCP, AN UNUSUALLY VERSATILE PEROXIREDOXIN - Reeves, Stacy A. (Wake Forest University, 2011)
In Escherichia coli, bacterioferritin-comigratory protein (EcBCP) by definition is a peroxiredoxin (Prx) which catalyzes the reduction of hydrogen peroxide and organic hydroperoxides. EcBCP is a member of the most poorly characterized and least studied Prx subfamily. The experiments and data presented in this thesis were undertaken to elucidate the biochemical features of this poorly characterized Prx found in E. coli. EcBCP is one of 3 Prxs utilized by E. coli as defenders against oxidative stress. Contradicting studies claim that EcBCP is capable of efficiently scavenging peroxides by two different peroxiredoxin mechanisms, 1-Cys and atypical 2-Cys. However, EcBCP may be capable of utilizing either mechanism when needed. Our investigations using analytical ultracentrifugation approaches demonstrated that both oxidized and reduced BCP behaved as monomers in solution at concentrations as high as 200 μM, thus eliminating the possibility of intermolecular disulfide bond formation and typical 2-Cys mechanisms. In fact, mutational studies of the resolving cysteine revealed a 1-Cys peroxidase mechanism was possible. During thioredoxin-dependent peroxidase activity studies conducted by stopped flow spectroscopy, an increase in Vmax,app was observed with increasing reducing substrate concentrations, indicating a nonsaturable interaction with the reductant. At physiologically reasonable thioredoxin 1 (Trx1) concentration of 10 μM, the Km,app value for H2O2 is ∼80 μM, and overall Vmax/Km for H2O2, which remains constant over the various Trx1 concentrations, is about 1.3 x 104 M-1 s-1. Our kinetic analyses demonstrated the ability of BCP to utilize different reducing substrates, including Trx1, thioredoxin 2 (Trx2), glutaredoxin 1 (Grx1) and glutaredoxin 3 (Grx3). EcBCP exhibited an unexpectedly high redox potential of – 145.9 ± 3.2 mV, the highest recorded value for a Prx. The unusually high redox potential increases the versatility of EcBCP by broadening its pool of reductants. Moreover, this protein exhibited a broad specificity for peroxides, with comparable rates for H2O2 and cumene hydroperoxide. We have now shown that BCP is a stable enzyme exhibiting broad specificity for reductants and peroxide substrates, potentially allowing BCP to remain fully active and functional under varying cellular conditions. Additionally, spectroscopic and activity titration studies showed that the pKm,app of peroxidatic cysteine (Cys46) was ∼5.8, which is common among Prxs. The combination of these biochemical features and its ability to remain active highlights its cellular importance and suggests that EcBCP functions as a Prx stop–gap protein during times of increased oxidative stress.
Keywords: Bacterioferritin comigratory protein; disulfide redox centers; peroxidases; peroxiredoxins; redox potential